2020
DOI: 10.1684/epd.2020.1203
|View full text |Cite
|
Sign up to set email alerts
|

The brain as a complex network: assessment of EEG‐based functional connectivity patterns in patients with childhood absence epilepsy

Abstract: The human brain is increasingly seen as a dynamic neural system, the function of which relies on a diverse set of connections between brain regions. To assess these complex dynamical interactions, formalism of complex networks was suggested as one of the most promising tools to offer new insight into the brain's structural and functional organization, with a potential also for clinical implications. Irrespective of the brain mapping technique, modern network approaches have revealed fundamental aspects of norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 74 publications
3
12
0
Order By: Relevance
“…To this end, we combined advanced high-frequency functional multicellular imaging using a novel stable and bright low-affinity Ca 2+ probe with classical physiological analyses, as well as functional and multilayer network tools [13,25,[52][53][54][55][56][57]. The latter have proven to be a much richer computational framework than classical network analyses and particularly suitable for the description of time-varying networks and for exploring the temporal robustness of functional connectivity patterns [25,[58][59][60][61][62][63]. Representing the spreading Ca 2+ waves in islets of Langerhans as network layers, to the best of our knowledge for the first time, enabled us to interpret the effects of NMDAR inhibition on the multicellular level of beta cell activity, far beyond classical physiological and network methods for cellular signaling analysis.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we combined advanced high-frequency functional multicellular imaging using a novel stable and bright low-affinity Ca 2+ probe with classical physiological analyses, as well as functional and multilayer network tools [13,25,[52][53][54][55][56][57]. The latter have proven to be a much richer computational framework than classical network analyses and particularly suitable for the description of time-varying networks and for exploring the temporal robustness of functional connectivity patterns [25,[58][59][60][61][62][63]. Representing the spreading Ca 2+ waves in islets of Langerhans as network layers, to the best of our knowledge for the first time, enabled us to interpret the effects of NMDAR inhibition on the multicellular level of beta cell activity, far beyond classical physiological and network methods for cellular signaling analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Epileptic seizures were considered the result of hypersynchronous and abnormal discharges among neurons. It was found that the synchronicity of neural activity was enhanced during ictal episodes (6). Some scholars have reported that hypersynchronized neuronal activity increases the chance of epileptic discharges and eventually leads to epileptic seizures (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The brain can be seen as a complex network in which nodes of a network represent brain areas, and edges reflect either structural or functional connections between different nodes (6). An increasing amount of evidence has indicated that epilepsy is a network disease and that epileptic discharges spread to the whole brain through the network (6,(13)(14)(15). Previous studies have also revealed altered functional and structural networks in patients with epilepsy (13,(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of EEG we can assign distinct layers to different time windows and/or different frequency bands and assign each electrode to a node in each single-layer network. For example, a time-based multilayer complex network analysis was perfomed on EEG recordings in patients with epilepsy (Leitgeb et al, 2020). The central issues in multilayer network based methods for EEG signal is to find a representation that minimizes information loss and introduce suitable statistical tools to extract readable information from the networks.…”
Section: Introductionmentioning
confidence: 99%